HIV-1 escape from the CCR5 antagonist maraviroc associated with an altered and less-efficient mechanism of gp120-CCR5 engagement that attenuates macrophage tropism - Roche, M.; Jakobsen, M.; Sterjovski, J.; Ellett, A.; Posta, F.; Lee, B.; Jubb, B.; Westby, M.; Lewin, S.; Ramsland, Paul; Churchill, M.; Gorry, P. (2011)
Maraviroc (MVC) inhibits the entry of human immunodeficiency virus type 1 (HIV-1) by binding to and modifying the conformation of the CCR5 extracellular loops (ECLs). Resistance to MVC results from alterations in the HIV-1 gp120 envelope glycoproteins (Env) enabling recognition of the drug-bound conformation of CCR5. To better understand the mechanisms underlying MVC resistance, we characterized the virus-cell interactions of gp120 from in vitro-generated MVC-resistant HIV-1 (MVC-Res Env), comparing them with those of gp120 from the sensitive parental virus (MVC-Sens Env). In the absence of the drug, MVC-Res Env maintains a highly efficient interaction with CCR5, similar to that of MVC-Sens Env, and displays a relatively modest increase in dependence on the CCR5 N terminus. However, in the presence of the drug, MVC-Res Env interacts much less efficiently with CCR5 and becomes critically dependent on the CCR5 N terminus and on positively charged elements of the drug-modified CCR5 ECL1 and ECL2 regions (His88 and His181, respectively). Structural analysis suggests that the Val323 resistance mutation in the gp120 V3 loop alters the secondary structure of the V3 loop and the buried surface area of the V3 loop-CCR5 N terminus interface. This altered mechanism of gp120-CCR5 engagement dramatically attenuates the entry of HIV-1 into monocyte-derived macrophages (MDM), cell-cell fusion activity in MDM, and viral replication capacity in MDM. In addition to confirming that HIV-1 escapes MVC by becoming heavily dependent on the CCR5 N terminus, our results reveal novel interactions with the drug-modified ECLs that are critical for the utilization of CCR5 by MVC-Res Env and provide additional insights into virus-cell interactions that modulate macrophage tropism. © 2011, American Society for Microbiology.